1985
DOI: 10.1088/0022-3727/18/8/030
|View full text |Cite
|
Sign up to set email alerts
|

Thermoluminescence studies in LiF dosimeter irradiated at 77K and their implications on theoretical models

Abstract: In LiF:Mg, Ti dosimeters, gamma -irradiation at low temperature (77K) reduces the TL intensities of peaks 7 (260 degrees C) and 10 (450 degrees C) drastically whereas the TL intensity of peak 5 (200 degrees C) remains nearly the same as that after irradiation at room temperature (RT). This implies that during irradiation, interstitial migration is involved in the formation of traps giving rise to peaks 7 and 10. The generic nature of peaks 7 (Z2) and 10 (Z3) traps and their (Z2 to or from Z3) trap conversion a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1986
1986
1998
1998

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Studies by many authors e.g., Refs,8,17,22,23,27,28 have indicated that the 5.5 eV band is thermally stable up to 400 °C whereupon its thermal destruction appears to correlate with the appearance of TL peak 10. Studies by many authors e.g., Refs,8,17,22,23,27,28 have indicated that the 5.5 eV band is thermally stable up to 400 °C whereupon its thermal destruction appears to correlate with the appearance of TL peak 10.…”
mentioning
confidence: 98%
“…Studies by many authors e.g., Refs,8,17,22,23,27,28 have indicated that the 5.5 eV band is thermally stable up to 400 °C whereupon its thermal destruction appears to correlate with the appearance of TL peak 10. Studies by many authors e.g., Refs,8,17,22,23,27,28 have indicated that the 5.5 eV band is thermally stable up to 400 °C whereupon its thermal destruction appears to correlate with the appearance of TL peak 10.…”
mentioning
confidence: 98%
“…14 However, absorption bands at 380, 310, and 280 nm become visible, mainly above 252 K, in addition to the bands at 250 and 200 nm. It is interesting to note that the F band which appears in the optical absorption spectra obtained at 252 and 273 K presents a lower relative intensity, when these spectra are compared with that determined with a room temperature irradiated TLD-100 single crystal, see Lakshmanan et al, 3 Da Rosa and Caldas. 15 For room temperature irradiated samples, the F band is the most prominent one.…”
Section: Results and Commentsmentioning
confidence: 97%
“…Based upon results from Nepomnyashchikh and Radzhabov, 16 F centers are not easily formed when LiF samples are irradiated at temperatures near 77 K. It should be mentioned that the band at 280 nm does not appear clearly in the optical spectrum determined with a room temperature irradiated TLD-100 single crystal. 3,15 …”
Section: Results and Commentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even if one assumes that only some Mg ÷ centres change to Mg ° centres, then the peak 10 (correlated with 225 nm OA) TL in virgin LiF TLD-100 should have been considerably greater than that for the 140°C preirradiation annealed sample, because peak 5 (correlated with 310 nm OA) TL traps and hence the electrons released from them are a factor of 20 to 30 times higher in the former sample than in the latter one. But experiments show no appreciable difference in peak 10 TL between the two samples (Lakshmanan et al 1985). (4) In § 4.1 of paper I, it is also mentioned that ESR measurements by Watterich et al (1980) show that in LiF:Mg, the 0 value is 2.006 for the F band and 2-029 for the 225 nm band suggesting that the latter is not a Za band.…”
Section: Thermoluminescence Of Alkali Halides Doped With Alkaline Earmentioning
confidence: 91%